Pengaruh Pengungkapan Islamic Social Reporting terhadap Earnings Response Coefficient - Ari Sita Nastiti (Universitas Jember, 2017)
This study examines the relationship between Islamic Social Reporting (ISR) disclosure that is published in annual report and informativeness of earnings (as measured by Earnings Response Coefficient/ERC). The hypothesis predicts that ISR disclosure will effect on the level of ERC. The sample consists of 95 annual reports of the companies listed on Indonesia Sharia Stock Index on December 2014. The amount of ISR disclosure provided in annual reports is measured by disclosure items developed by Othman et al. (2009). The hypothesis is tested by using multiple regression analysis. The empirical results of the study show that the level of ISR disclosures significantly has positive effect on the ERC. The results indicate that investor uses the information of ISR disclosure that is provided in annual report together with information in earnings as one of the guidance for their investment decisions. The study contributes to the literature that ISR is an important information to be disclosed by company because it can increase the level of investor’s belief toward the information of earnings reported. Keywords: Earnings Response Coefficient, Indonesia Sharia Stock Index, Informativeness of Earnings, Islamic Social Reporting